PENGARUH MEDIA SOSIAL INSTAGRAM @AWKARIN TERHADAP GAYA HIDUP HEDONIS DI KALANGAN FOLLOWERS REMAJA - Rizka Monanda; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Social media instagram is a new media that is currently in great demand by the people of Indonesia. @awkarin’s Social media Instagram as one of the accounts deemed viral and followed by millions of teenagers in Indonesia can affect the activities, interests, opinions, and lifestyle of its users. Hedonis lifestyle is a lifestyle whose activities to seek pleasure of life, such as spending more time outdoors, playing more, happy in the city crowd, happy to buy the expensive goods that he likes, and always want to be the center of attention. The purpose of this study is to find out theu influence of @awkarin’s social media instagram against hedonic lifestyle among adolescent followers by using S-O-R theory as the foundation. This research uses quantitative research method with explanation approach. This research was conducted by sending questionnaires to @awkarin’s social media instagram followers through online. Respondents in this research are 100 people who follow social media instagram @awkarin and the category is determined based on random sampling. Data collection is obtained through questionnaires and documentation. Data analysis technique in this research is quantitative analysis. The results of this study indicate that influential @awkarin’s Social Media Instagram against hedonic lifestyle among adolescent followers. Proved by the value of regression coefficient in this study is Y = 4,043 + 0.695X. the constant number of 4,043 and the coefficient of social media value variable is 0.695. meanwhile t count 4.043 bigger when compared with t table equal to 1667, with level significance 0.000 smaller than α = 0,05. Based on the table "Model Summary" shows that the value of R = 0.543 and the coefficient of determination (Rsquare) is 0.294. This figure indicates that the contribution of social media variable @Awkarin’s instagram to visiting followers interest is 29.40%. @Awkarin’s Social media instagram influences the Hedon lifestyle among adolescent followers, and the magnitude of influence with the "low" category.Keywords: Influence, Social Media, Hedonis Lifestyle